Improving the safety and well-being of domestic abuse survivors: the role of a specialist organisation in supporting the work of Independent Domestic Violence Advisors - Taylor-Dunn, Holly (Crime prevention and community safety, 2021)
Over the last 15 years, successive UK Governments have promoted the role of Independent Domestic Violence Advisors (IDVAs) in addressing the safety of (primarily) women affected by domestic abuse. Limited evaluations of IDVA services exist, with evidence suggesting women report improved safety and well-being as a result of specialist support. To date, however, little attention has been paid to the organisations in which IDVA services are based, despite recommendations that specialist domestic abuse organisations are the most appropriate home for IDVAs. This article draws on findings from the evaluation of an IDVA service in England to explore firstly, the outcomes achieved by the service and secondly, the extent to which the organisation facilitated IDVA support through its values, principles, policies and procedures. Finally, the article reflects on what these findings mean for the effective delivery of domestic abuse services.